IMPLEMENTASI STANDAR NASIONAL INDONESIATEMBAKAUMEMERLUKAN KOMITMEN SEMUA PIHAK - Samsuri Tirtosastro; Widowati Widowati (Universitas Tribhuwana Tunggadewi, 2016)
IHT, manufacturing industry which use domestic raw material, mix of art (blending) the original tobacco, cloves, sauces and other as ingredients. IHT products (cigarettes, cigars, shag) is a sensory product, based on flavor and aroma subjectively, corresponding in well-ordered quality grade of raw tobacco. More than 25 variety has been prepared by SNI and it will distribute, carried out by some employers when it take purchase tobacco from farmers, then collect using BSN (Institution of National Standardization) format. Implementation of SNI-Tobacco should happen carefully in site of selection, determination varieties, cultivation and processing techniques in the way of trade presentation. Planting in a. One variety, b. technology of recommend packages of consumers while it will implement correctly, and c. mutual commitment between farmers and entrepreneurs of tobacco is the main foundation. The protection or shelter from the government, especially the local government through various regulations, is necessary. It will desire of all parties, specific for employers and tobacco farmers. However, adequate legal protection from SNI-Tobacco particularly in partnerships between farmers and entrepreneurs regulation can not be expected.